Low-Cost Real-Time Mobile Air-Quality Monitoring System (AQMS) - Amanina Binti Asim, Iman; Murizah Binti Kamarudin, Asma’; Onn, Munirah; Azeehan Azli¬, Shakira; Zainuddin, Aznilinda; Mohd Zain, Norlina; Kamarudin Hasan, Khairul (International Journal of Engineering and Technology, 2018)
Air quality is one of the dominant health and environmental interest issues in the world thus it is important to monitor air quality at surrounding area especially in big cities and urban areas. This paper explains the development of a reliable and cost-effective air quality monitoring system (AQMS) that can measure the air quality at indoor and outdoor area and to alert the user of the hazardous air quality index (AQI) level through an alarm system upon detection. By using Arduino platform and various sensors along with a flat-panel liquid-crystal display (LCD) and Bluetooth module, the system detects the level of the hazard gases, temperature and humidity of the area. The AQMS is a portable air quality index (AQI) acquisition device that is simple to carry and provide real-time measurement on the LCD. It is a user-friendly device and handy to operate. The AQMS gives the public an opportunity to monitor the air quality personally and helps to bring awareness on the real-time air quality around them and improve the air quality.